Targeted Gene Delivery: Where to Land - Pavani, Giulia; Amendola, Mario (Frontiers in Genome Editing, 2021)
Genome editing technologies promise to correct any disease-causing mutation involved in blood disorders. In particular, targeted gene insertion can correct different mutations affecting the same gene with a single therapeutic strategy (gene replacement), or provide novel functions to edited cells (gene addition). Targeting a selected genomic harbor not only reduces insertional mutagenesis risk, but allows to modulate disease-modifier genes and exploit endogenous promoters (or specific chromatin contexts) to achieve specific transgene expression levels/patterns. In this review, we will discuss the current limitations and potential risks of targeted gene insertion and the advantages and drawbacks of different genomic harbors currently under investigation for various gene therapy applications.